Mengurangi Cacat Color out Menggunakan Pendekatan Seven tools: Studi Kasus Industri Coloring Compound Plastic - Irwati, Dwi; Prasetya, Dwi Indra (JURNAL TEKNIK INDUSTRI, 2020)
Kaizen or continuous improvement is an integral part of the implementation of Total Quality Management (TQM). Kaizen is a continuous improvement and has the goal of increasing work safety, quality, productivity and costs. Kaizen can improve product efficiency and quality. This study aims to show the effective application of seven tools as a quality. This study aims to show the effective application of seven tools as a quality management tool to reduce color defects in the process of coloring and compounding the plastic pellets. Where the seven tools approach plays an important role as quality management tools in the kaizen process in the company. The case study was carried out by a plastic seed coloring and compounding company located in Bekasi. The high rework process and the cost of color correction due to color out defects are considered to be one of the causes of reduced company profits. Based on data processing using the seven tools approach and the improvements made, there were significant savings.